2021
DOI: 10.1136/bmjhci-2020-100262
|View full text |Cite
|
Sign up to set email alerts
|

Applying natural language processing and machine learning techniques to patient experience feedback: a systematic review

Abstract: ObjectivesUnstructured free-text patient feedback contains rich information, and analysing these data manually would require a lot of personnel resources which are not available in most healthcare organisations.To undertake a systematic review of the literature on the use of natural language processing (NLP) and machine learning (ML) to process and analyse free-text patient experience data.MethodsDatabases were systematically searched to identify articles published between January 2000 and December 2019 examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 49 publications
1
49
0
Order By: Relevance
“…A comprehensive study of sentiment analysis in a social media platform for health care confirmed the contradictory findings of prevalent views [ 29 ]. Furthermore, additional systematic studies indicate that the polarity of sentiments was affected by the corpus- and thesaurus-based techniques employed in the research [ 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A comprehensive study of sentiment analysis in a social media platform for health care confirmed the contradictory findings of prevalent views [ 29 ]. Furthermore, additional systematic studies indicate that the polarity of sentiments was affected by the corpus- and thesaurus-based techniques employed in the research [ 28 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, evaluating the relationship between quality dimensions derived from social media reviews and patient satisfaction as measured by prior studies [ 35 , 70 ]. In addition, a comparison of the labeled dataset used in this study to other dictionaries or tools used in prior studies to enhance sentiment and text classification would be beneficial [ 28 , 29 ]. Further, future research may include other social media platforms (e.g., Twitter, Instagram, Tik-Tok, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NLP often uses machine learning to make sense out of social media comments. 2 One problem with using reviews on social media for making decisions is that sometimes reviews are fake, and reviews on social media websites, while widely accepted by consumers, are not automatically legitimate. 3…”
Section: Social Media/patient Interactionmentioning
confidence: 99%